Penerapan Algoritma Reed Solomon Pada Sistem Informasi Absensi Pegawai Diskominfo Lahat - Ajeng Sri Firliani; Ahmad Mutatkin Bakti (SMATIKA JURNAL : STIKI Informatika Jurnal, 2022)
The use of the absent system at Diskominfo Lahat Regency still uses a manual system in the form of a signature in the file attachment. With a system like this, of course, there are shortcomings in terms of efficiency, ranging from time, energy, and cost efficiency. The purpose of this study was to develop an attendance information system at the Lahat Communications and Information Office so that it could improve the time efficiency and performance of Lahat Diskominfo employees. The method used in the development of this system is an error correction algorithm that is often used in QR-Codes is the Reed Solomon Code algorithm. QR-Code equipped with error correction will be resistant to data corruption to a certain extent. Reed Solomon Algorithm (RS) is a channel-coding correction algorithm that functions to detect and correct a data packet. The benefits of developing an attendance information system that can support the attendance process are indispensable for the Department of Communication and Information in Lahat Regency. A web-based information system and has implemented the QR-Code feature supported by the Reed Solomon algorithm needs to be implemented in order to improve efficiency and performance. As well as being able to build an information system that can help the Department of Communication and Information in Lahat Regency in carrying out attendance, the researchers intend to build an application entitled Application of the Reed Solomon algorithm on the Lahat Diskominfo employee attendance information system. The result of this study is an attendance system that already uses QR-Code and the Reed Solomon Algorithm as an error detector in the code.